Effect of the North Atlantic Oscillation on groundwater recharge in karst aquifers of the Cilento Geopark (Italy) - Manna F.; Allocca V.; Fusco F.; Napolitano E.; De Vita P. (2013)
The assessment of groundwater recharge for aquifers of a Geopark is an essential issue to plan water management based on balancing both human uses and river ecology. The relevance of this topic is enhanced by the climatic variability which constraints to analyze water budget with a non-stationary methodology. In this paper, an approach for evaluating the effects of climatic variability on the groundwater recharge of karst aquifers of the Cilento Geopark is proposed, focusing on the influence of the North Atlantic Oscillation (NAO). Such karst aquifers store invaluable groundwater resources feeding settlements of the Geopark and maintaining ecological equilibrium of the main rivers. With such purpose, time series of annual precipitation and air temperature, recorded by a meteorological network covering the Cilento Geopark, were gathered for the period 1921-2010 and analyzed. The most important result is the finding of a complexly cyclical variability of precipitation, with periodicities from yearly to decadal, which is strongly correlated to the NAO. During the examined period, the annual precipitation and effective precipitation ranged around the mean value, respectively for about ±40% and ±70%. Due to the continental influence of the NAO, the proposed approach can be conceived as being extendable to other Geoparks, climatically controlled by the NAO, in which the management of the groundwater resources is crucial for river ecological systems. © Società Geologica Italiana, Roma 2013.